NONUNIFORM NUMERICAL GRID FOR THE NUMERICAL SOLUTION OF THE SCHRÖDINGER EQUATION - BORBÉLY, Sandor (Studia Universitatis Babeș-Bolyai Physica, 2016)
In the present work the numerical grids used during the numerical solution of the Schrödinger equation will be investigated. It will be shown, that by employing a nonuniform optimized numerical grid the number of gridpoints and implicitly the computational effort for the solution of the Schrödinger equation can be significantly reduced. As a test system the harmonic oscillator, and the finite-elements discrete variable representation (FEDVR) numerical will be used, but the obtained results can be extended to other systems and numerical grids too.